Inter-relações entre os influenciadores do intraempreendedorismo - Baldissera, Helem Cristina (2019)
Innovation is a key factor for better organizational performance, a fact that leads companies to look for ways to promote constant innovation. Among the possibilities for promoting innovation, intrapreneurship is presented as a practice that inserts employees in the innovative process and allows them to act as internal entrepreneurs, favoring the emergence of innovations. The occurrence of intrapreneurship relies on the interaction of two main influencers, the organizational factors and entrepreneurial behavior, being that the organizational commitment was inserted in the theme, because it is a bond that permeates the behavior of employees and the way they perform their activities within the organization. This research had as general objective “To analyze the relationships among the influencing aspects of intrapreneurship according to collaborators and managers of software development organizations in southwestern Paraná”. Six companies formed the research population, which was operationalized in two phases. The first phase was quantitative by applying structured questionnaires to a sample of 195 employees, and techniques of descriptive statistics analysis and structural equation modeling Entrepreneurial Behavior (EB), Organizational Factors of Intrapreneurship (OFI) and Organizational Commitment (OC) were analyzed. The second phase of the qualitative approach was developed with the company managers, who participated in a semi-structured interview based on quantitative results, having content analysis as a technique of analysis. The quantitative results showed significant and positive relationships among the analyzed constructs with greater effect on the relationship between OFI and OC. The OC, as a mediator variable, increased the direct effect between OFI and EB through partial mediation. The qualitative analysis identified that: actions are taken by companies that converge with the guidelines for the occurrence of intrapreneurship, there is the perception of managers that employees are affectionately committed to the company and the expression of the importance of human capital for organizations. Overall, it is noteworthy that the relationships found among OFI, EB and OC corroborate the discussion about the influencers for the occurrence of intrapreneurship as well as the role that EB plays among the organizations' incentive practices and the desired behaviors from workers. It was concluded that it was possible to observe the presence of the influencers in the organizations investigated, however intrapreneurship does not occur in them in an institutionalized manner, still, the existence of aspects that influence intrapreneurship may facilitate its eventual occurrence in a deliberate manner. That said, it is proposed the research design of this dissertation for future investigations with the participation of all employees of the company, including them in the qualitative analysis, and the use of other sectors of activity as population. The main limitation of the work is that its results are restricted to the participating organizations and cannot be generalized.